Biomarkers in Adult Dermatomyositis: Tools to Help the Diagnosis and Predict the Clinical Outcome. (14th January 2019) - Cassius, Charles; Le Buanec, Hélène; Bouaziz, Jean-David; Amode, Reyhan
Abstract : Dermatomyositis pathophysiology is complex. In recent years, medical research has identified molecules associated with disease activity. Besides providing insights into the driving mechanisms of dermatomyositis, these findings could provide potential biomarkers. Activity markers can be used to monitor disease activity in clinical trials and may also be useful in daily practice. This article reviews molecules that could be used as biomarkers for diagnosis and monitoring dermatomyositis disease activity.